Visceral leishmaniasis and pseudomonas septicemia associated with hemophagocytic syndrome and myelodysplasia in a Turkish child - Sipahi, Tansu; Tavil, Betül; Oksal, Ayşegül (The Turkish Journal of Pediatrics, 2005)
An 18-month-old boy presented with fever, hepatosplenomegaly, jaundice, pancytopenia, hyperferritinemia, hypertriglyceridemia and evidence of hemophagocytosis and trilineage myelodysplasia in the bone marrow aspiration. Appropriate treatment was begun but he died after 12 hours of hospitalization due to Gram-negative septicemia. Post-mortem examination of liver biopsy revealed diffuse hemaphagocytic lymphohistiocytosis and Leishmania-donovani bodies in macrophages.